Rancang Bangun Aplikasi Pemetaan Digital Pada Universitas Muhammadiyah Riau - Royan Choiro Yahya; Harun Mukhtar; Regiolina Hayami; Mitra Unik (Universitas Muhammadiyah Riau, 2020)
The campus area is a place for students and teaching staff to carry out their routine activities. But there are times when campus visitors are not only focused on teaching staff or students who already know the ins and outs of the campus area. Some parties such as students' parents, new students, guests sometimes need a certain guide to find specific areas of interest in the campus area. The development of this application is carried out aiming to assist and alleviate these parties to search and find related areas. The design of the software is made with Adobe Edge Animation CC with Action Script 3.0. based on the results of this study it can be concluded that the Digital Mapping Application on the Muhammadiyah Riau Campus can overcome the problem of confusion among the parties when visiting the Muhammadiyah Riau campus.